The Effect of Cartoon Movie on Students’ Speaking Ability - Syarifah Aini; Asnawi (Education & Learning, 2021)
The objective of the research was to determine whether there was a significant effect of the use of digital systems on the speaking skills of the students in Seventh Grade Junior High School. This research was a quantitative research with a quasy experimental design. It was conducted in seventh grade SMP Negeri 5 Tanjungbalai in the academic year 2020/2021. The total population was 93 students and researchers took 30 students for the experimental class and 30 students for the control class which meant 60 students as a total sample. In collecting data, researchers used orraly tests by speaking about the plot of the cartoon as instruments. Tests were pre-tests given before treatment and post tests given after treatment. Then, the data obtained were analyzed using t-test ar SPSS 16 with a significance level of 5% (0.05). Furthermore, the researcher found that the post –test mean score in the experimental class was higher than the control class (6.484 > 1.688). At a significant level of 5% (95% confidence level) which shows the score 18,976. The t-test result also showed that t0 (6.484) was higher than t table as a significance level of 5% (1.688). Therefore, the results of t0 > t table result that H0 (null hypothesis) was rejected and Ha (alternative hypotheiss) was accepted. The calculation of the effect size was 1.68 which was within the range of effect criteria including the strong effect. Thus, the use of the cartoon movie has a signficant effect on students’ speaking ability in the seventh grade students of SMP Negeri 5 Tanjungbalai in academic year 2020/2021.